Effects of propolis supplementation during cryopreservation of ram semen - Gungor, I. H.; Kaya, S. Ozer; Cinkara, S. Dayan; Cihangiroglu, A. cakir; Kaya, E.; Acisu, T. C.; Turk, G. (Shiraz Univ, 2024)
Background: Cryopreservation of ram semen is a very challenging process. Loss of motility during freezing does not allow artificial insemination of rams. Aims: This study aimed to determine whether the inclusion of liquid propolis extract in semen diluents affects the cryopreservation efficiency of ram semen. Methods: Six Akkaraman breed rams were considered for semen study. Semens were combined with Tris+egg yolk extender containing and without (control) propolis at different concentrations (0.25%, 0.50%, 1%, 2%, and 4%). Semen was frozen using routine ram semen freezing procedures. After thawing, motility and kinematic parameters were analyzed by computer assisted semen analysis (CASA), and viability, acrosomal damage level and mitochondrial membrane potential were analyzed by flow-cytometer in all groups. Additionally, fatty acid levels in total semen were analyzed using gas chromatography (GC), and vitamin and cholesterol levels were analyzed using high-performance liquid chromatography (HPLC). In addition, oxidative stress, HOS test, and morphological analyzes were performed after freezing and thawing. Results: The 0.5% propolis group showed a significant increase in total and rapid motility, LIN, membrane integrity, and antioxidant levels compared to the control, and a significant decrease in malondialdehyde (MDA) and low mitochondrial membrane potential (LMMP) levels. Compared to the control, the group containing 4% propolis damaged spermatozoa and caused a significant decrease in total, progressive and rapid motility and high mitochondrial membrane potential (HMMP), Glutathione S-transferase (GST), and catalase (CAT) levels. Conclusion: We showed that adding 0.5% propolis to semen extenders to increase the freezability level of ram semen increases the survival of spermatozoa after freeze-thaw and ensures the success of freezing.
Keywords: CASA; Flow-cytometer; Propolis liquid extract; Ram; Semen